EFISIENSI BIAYA MELALUI PEMANFAATAN TRANSPORTATION METHOD - Elfreda Aplonia Lau (DEDIKASI : Jurnal Ilmiah Sosial, Hukum, Budaya, 2021)
This study was conducted to find out whether the transportation costsof cement at PT. Bosowa in 2020 to distribute cement from Palaran andBalikpapan storage warehouses to markets that require it, namely Handil,Samboja, Samarinda and Spaku, can be saved or streamlined by usingtransportation methods. It also proves whether the temporary load allocationusing the North West Corner Method has provided the optimum solution orwhether it must be accompanied by optimal testing.The theoretical basis used in this study is management accountingtheory which emphasizes cost efficiency and transportation theory whichpresents transportation methods.The analytical tool used in this study is the North West Corner Method(NWCM) to allocate temporary loads while the optimal allocation uses theStepping Stone Method.The findings of this study indicate that the use of the North WestCorner Method of temporary load allocation does not necessarily result inoptimal load allocation and determination of transportation costs, thereforeit is necessary to test the temporary load allocation using the stepping stonemethod or the modified distribution method. Transportation Method isproven to be able to streamline cement transportation costs at PT. BosowaSamarinda branch in 2020.